Constitutional Review Of Administrative Actions: Development In United Kingdom, India, Malaysia, South Africa And Hong Kong - Normawati Binti Hashim (Sociological Jurisprudence Journal, 2019)
The 21st century saw the rapid development of the administration of the nations of the world. With the development, it is essential to ensure that administrator entrusted with the administration of the country perform its duties in accordance with the rule of law. It must not act arbitrarily. Discretionary power if given to the administrator, it is limited. This is to guarantee that administrator in performing its duties would not infringe rights of an individual or community, especially fundamental rights. To make certain that this is achieved, an effective mechanism for the protection of rights, especially human or fundamental rights in state administration is needed. Judicial review is one of the effective mechanism to supervise and control action of the administrator. This mechanism is available in Administrative Law. Under the instrument, grounds of judicial review is made available to review action of the administrator. Currently, there are two streams of judicial review: Administrative Review and Constitutional Review. The former is a non-right based review of administrator’s power founded on the traditional common law using Wednesbury objective test or CCSU grounds not involving violation of fundamental and human right and the procedures. Meanwhile, the latter is a right-based review involving the exercise of administrative powers that violate the constitutional right of an individual or community, particularly, fundamental rights. The traditional common law, nevertheless, are inadequate in addressing review of administrative action involving violation of fundamental rights. For that reasons constitutional review as another stream in judicial review was developed. This was illustrated looking into the development in United Kingdom, India, Malaysia, South Africa and Hong Kong. With the expansion, mentioned the common law countries are capable of providing a more comprehensive and meaningful protection to an individual or community against unlawful act of the administrator that violates rights, especially human and fundamental rights. Consequently, state integrity is strengthen and be more accountable to the community. Hence, state can develop administration that is sound, and efficient in human, natural, economic and financial management. The proper enforcement of human rights will promote political and socio-economic stability, provide legal certainty and it encourages investors to invest in the country.